Application of multivariate statistical analysis to assess browning susceptibility in sweet potatoes (Ipomoea batatas (l.) Lam.) cultivars, based on chemical and enzymatic determinations - Ojeda, G. A. (2019)
The selection of a sweet potato cultivar for minimal processing must be performed considering the nutritional value and the lower susceptibility to browning development, which will result in greater stability of the vegetable colour. The aim of this work was to evaluate browning susceptibility in four sections of two sweet potato cultivars combining chemical and enzymatic determinations with colour variables, by applying multivariate statistical techniques. Each cultivar had a characteristic browning pattern; in white cultivar colour changes were represented by changes in variable b* while in the red cultivar these changes responded to variations in variable a* .The regions with major colour changes (ΔE* >6) after 24 hours also had high levels of phenolic compounds (658±98 mg chlorogenic acid/kg fresh tissue) and high oxidative enzymes activities. Principal Component Analysis indicated that three regions in white cultivar and two in red cultivar had low browning susceptibility. Partial Least Square analysis indicated that colour changes (ΔE* ) were highly associated with Polyphenoloxidase activity and phenolic compounds. By comparing both cultivars analyzed, the white cultivar presented 3 regions with low browning susceptibility and therefore would be more suitable for minimally processing. This low susceptibility would be related to low phenol content and lower enzyme activities.